DNA Code Design Based on the Bloch Quantum Chaos Algorithm - Qingji Guo; Bin Wang; Changjun Zhou; Xiaopeng Wei; Qiang Zhang (IEEE Access, 2017)
The design of DNA codes sets satisfying certain combinatorial constraints is important in reducing hybridization errors due to nonspecific hybridization between distinct codes and their complements in DNA computing, data encryption, and data storage. The DNA code design problem is to find the largest possible set of DNA codes. In this paper, we present a Bloch quantum chaos algorithm for the designing DNA codes sets. The algorithm uses the chaotic equation to initialize the Bloch coordinates of quantum bits, next adopts the whole interference crossover strategy to get crossover operation, then employs quantum non gate strategy to get mutation operation, finally utilizes the dynamic adjustment strategy to adjust the quantum rotation corner. Several experimental results in which our algorithm finds DNA codes sets match or exceed the best previously known constructions.